MULTIDIMENSIONAL GIBBS DISTRIBUTION AND AN IDEAL GAS OF NON-RELATIVISTIC PARTICLES - Kusevich, A. E.; Eingorn, M. V.; Zhuk, A. I. (Одеські астрономічні публікації, 2011)
We generalize the standard methods of quantum statistical physics and thermodynamics to the multidimensional case and apply them in order to derive different thermodynamic quantities, characterizing an ideal gas of non-relativistic particles. In particular, we obtain the formula for the pressure in the internal space.